Numerical Investigations on Residual Stress in Laser Penetration Welding Process of Ultrafine-Grained Steel. (26th December 2018) - Liu, Dezheng; Li, Yan; Liu, Haisheng; Wang, Zhongren; Wang, Yu
Abstract : Weld solidification crack prevention in the laser penetration welding process is essential for the strength of the welded component. The formation of solidification cracks can ultimately be attributed to welding residual stresses, and preventive measures should be taken during welding. In this study, the effects of residual stresses on the laser penetration welding quality of ultrafine-grained steels were investigated. A heat source model was established through the analysis of the metallography of the cross section of the heat-affected zone (HAZ) of ultrafine-grained AN420s-grade steel, and the chemical composition of the weld bead was obtained using an FLS980-stm Edinburgh fluorescence spectrometer. Furthermore, the constitutive coupling relation between the temperature and material flow stress was established based on the Gibbs function, and the welding residual stress was obtained by setting trace points in a finite element analysis (FEA) model based on experimental data of the weld bead cross section under different welding conditions. The results show that weld solidification cracks will form when the residual stresses exceed the material flow stresses in the weld bead, and the residual stresses can be decreased through a reasonable increase of the welding speed. The results indicate that the proposed criterion has high accuracy and can be used to predict the formation of weld solidification cracks in the laser penetration welding process.